Drug adherence and multidisciplinary care in patients with multiple sclerosis: Protocol of a prospective, web-based, patient-centred, nation-wide, Dutch cohort study in glatiramer acetate treated patients (CAIR study) - Siepman Theodora; de Schryver Els; Samijn Johnny; van Munster Eric; van Huizen Marc; Hoogervorst Erwin; Vliegen Joseph H; Gilhuis Job; Schrijver Hans; Hupperts Raymond; Hengstman Gerald; Jongen Peter J; et al. (BMC Neurology, 2011)
Abstract Background Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system, for which no definitive treatment is available. Most patients start with a relapsing-remitting course (RRMS). Disease-modifying drugs (DMDs) reduce relapses and disability progression. First line DMDs include glatiramer acetate (GA), interferon-beta (INFb)-1a and INFb-1b, which are all administered via injections. Effectiveness of DMD treatment depends on adequate adherence, meaning year-long continuation of injections with a minimum of missed doses. In real-life practice DMD-treated patients miss 30% of doses. The 6-month discontinuation rate is up to 27% and most patients who discontinue do so in the first 12 months. Treatment adherence is influenced by the socio-economic situation, health care and caregivers, disease, treatment and patient characteristics. Only a few studies have dealt with adherence-related factors in DMD-treated patients. Self-efficacy expectations were found to be related to GA adherence. Patient education and optimal support improve adherence in general. Knowledge of the aspects of care that significantly relate to adherence could lead to adherence-improving measures. Moreover, identification of patients at risk of inadequate adherence could lead to more efficient care. In the near future new drugs will become available for RRMS. Detailed knowledge on factors prognostic of adherence and on care aspects that are associated with adequate adherence will improve the chances of these drugs becoming effective treatments. We investigate in RRMS patients the relationship between drug adherence and multidisciplinary care, as well as factors associated with adherence. Given the differences in the frequency of administration and in the side effects between the DMDs we decided to study patients treated with the same DMD, GA. Methods/design The Correlative analyses of Adherence In Relapsing remitting MS (CAIR) study is an investigator-initiated, prospective, web-based, patient-centred, nation-wide cohort study in the Netherlands. The primary objective is to investigate whether GA adherence is associated with specific disciplines of care or quantities of specific care. The secondary objective is to investigate whether GA adherence is associated with specific aspects of the socio-economic situation, health care and caregivers, disease, treatment or patient characteristics. All data are acquired on-line via a study website. All RRMS patients in the Netherlands starting GA treatment are eligible. Patients are informed by neurologists, nurses, and websites from national MS patient organisations. All data, except on disability, are obtained by patient self-reports on pre-defined and random time points. The number of missed doses and the number of patients having discontinued GA treatment at 6 and 12 months are measures of adherence. Per care discipline the number of sessions and the total duration of care are measures of received care. The full spectrum of non-experimental care that is available in the Netherlands is assessed. Care includes 'physical' contacts, contacts by telephone or internet, health-promoting activities and community care activities. Care received over the preceding 14 days is assessed by patients at baseline and every other week thereafter up to month 12. Every 3 months neurologists and nurses record care disciplines to which patients have been referred. The Dutch Adherence Questionnaire-90 (DAQ-90) is a 90-item questionnaire based on the World Health Organisation (WHO) 2003 report on adherence and comprehensively assesses five domains of evidence-based determinants of adherence: socio-economic, health care and caregivers, disease, treatment, and patient-related factors. In addition, self-efficacy is assessed by the MS Self-Efficacy Scale (MSSES), and mood and health-related quality of life (HRQoL) by the Multiple Sclerosis Quality of Life-54 questionnaire (MSQoL-54). Relapses and adverse events probably or definitively related to GA are also reported. Discussion In this study data is mainly acquired by patients' self-reporting via the internet. On-line data acquisition by patients does not require study visits to the hospital and can easily be integrated into daily life. The web-based nature of the study is believed to prevent missing data and study drop-outs. Moreover, the automated process of filling in questionnaires ensures completeness and consistency, thus improving data quality. The combination of patient-reported outcomes, fully web-based data capture and nation-wide information to all eligible patients are distinguishing features of the study and contribute to its scientific potential. Trial registration Netherlands Trial Register (NTR): NTR2432